2022
DOI: 10.3390/medicina58101313
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Misfit of 3D-Printed (Selective Laser Sintered), CAD-CAM and Lost Wax Technique Cobalt Chromium Copings with Shoulder and Chamfer Finish Lines: An In-Vitro Study

Abstract: Background and Objectives: The aim was to compare the Misfit of 3D-Printed, Selective laser melting (SLM), milled (Computer aided design-Computer aided manufacture CAD-CAM) and Lost wax technique (LWT) fabricated Cobalt chromium (CoCr) alloy copings on shoulder (SH), radial shoulder (R-SH) and chamfer (CH) finish line configuration. Materials and Methods: Ninety resin, second maxillary premolar teeth were prepared for metal-ceramic crowns, equally divided into (n = 30) SH, R-SH and CH margin preparations. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Afterward, 12 articles were excluded because 5 studies analyzed the marginal and internal discrepancy values after completing ceramic veneering procedures, 1 investigation did not provide the quantitatively measured marginal and internal discrepancies, 3 studies did not provide the manufacturer of the metal printer used to fabricate the specimens, and 3 studies did not test metal AM techniques. A total of 31 articles (30 in vitro [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][55][56][57][58][59][60][61][62][63][64][65] and 1 clinical 54 ) were included in the present systematic review.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Afterward, 12 articles were excluded because 5 studies analyzed the marginal and internal discrepancy values after completing ceramic veneering procedures, 1 investigation did not provide the quantitatively measured marginal and internal discrepancies, 3 studies did not provide the manufacturer of the metal printer used to fabricate the specimens, and 3 studies did not test metal AM techniques. A total of 31 articles (30 in vitro [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][55][56][57][58][59][60][61][62][63][64][65] and 1 clinical 54 ) were included in the present systematic review.…”
Section: Study Selectionmentioning
confidence: 99%
“…The selected articles were classified based on the evaluation method used to assess the fit of the Co-Cr frameworks, namely manufacturing accuracy, 35,36 the dual-scan 37,38 and triple-scan method, 39 stereomicroscope, [40][41][42][43][44][45] optical coordinate measurement machine (CMM), 46 microCT, 47,48 profilometer, 49 and silicone replica technique. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Additionally, each group was subdivided into six subgroups based on the manufacturer used to fabricate the SLM Co-Cr frameworks, namely 3D Systems, 35,62 Bego, 51,54 Concept Laser, [37][38][39]41,42,47,48,52,56,58 EOS, 36,40,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding their biocompatibility, a study reported that ceramic materials offer better biocompatibility and cell response compared to polymers [ 17 ]. Many improved materials with superior mechanical qualities have been developed for CAD/CAM technology in the last decade [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. With the development of novel nanomaterials, the standards of dental care health also improved by altering the properties of biomaterials [ 26 ].…”
Section: Introductionmentioning
confidence: 99%